First, we are told that we get 3.6 more ounces than the original lotion, nis means that the new amount of lotion equals the amount in the original plus 3.6, then we can write the following expression:
new = original + 3.6
By calling "y" to the original tube content and "x" to the new tube content, we can rewrite the above expression, to get:
x = y + 3.6
We are also told that we are getting 30% more than we used to get, then we can formulate the following expression:
x = y + 0.3y
Where in the second term of the right side we are adding 30% of the original tube content.
Then we have a system of two linear equations and we have to solve for y, by subtracting the second equation from the first one, we eliminate x and we can solve for y like this:
x = y + 3.6
-x = -y -0.3y
--------------------
0 = 3.6 - 0.3y
From the equation 0 = 3.6 - 0.3y we can solve for y to get:
0 = 3.6 - 0.3y
0.3y = 3.6
y = 3.6/0.3
y = 12
Then, there were 12 ounces in the original tube